SPEECH ACT THEORY IN ARTHUR MILLER’S DRAMA “THE CRUCIBLE” - Mulyanto Mulyanto (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2019)
The research intends not only to describe the functions of the speech acts used by the main characters in Arthur Miller’s drama,The Crucible but also to identify the illocutionary of the speech actsand to identify the illocutionary and functions of the speech acts dominant in Arthur Miller’s drama, The Crucible. Based on the research findings, it is found that The first scene occurs at the beginning of Act II in John Proctor's house. The second scene occurs in Act IV in John Proctor's prison cell near the end of the play before he chooses to be hanged with honor rather than live with shame.  Both scenes include an act of request, to confess in the first instance or to approve of an act of confession in the second.  In both scenes, the hearer declines the request.